2022
DOI: 10.1093/femspd/ftac043
|View full text |Cite
|
Sign up to set email alerts
|

Pyp25α is required for male gametocyte exflagellation

Abstract: Malaria, a mosquito-borne infectious disease, is caused by the unicellular apicomplexan protozoa of the genus Plasmodium. For malaria parasite transmission, the essential sexual stage includes production of gametocytes through gametocytogenesis in vertebrate hosts and formation of gametes from gametocytes through gametogenesis in mosquito vectors. Whereas each female gametocyte forms a single immotile macrogamete, a male gametocyte produces eight flagella-like microgametes in a process called exflagellation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…An essential role of TPPP in the formation of flagella was demonstrated in Chlamydomonas reinhardtii , biflagellated green algae, through the use of null mutant of FAP265, its TPPP ortholog [ 7 ]. Very recently, it has also been shown that TPPP (Py05543) is required for male gametocyte exflagellation in Plasmodium yoelli [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…An essential role of TPPP in the formation of flagella was demonstrated in Chlamydomonas reinhardtii , biflagellated green algae, through the use of null mutant of FAP265, its TPPP ortholog [ 7 ]. Very recently, it has also been shown that TPPP (Py05543) is required for male gametocyte exflagellation in Plasmodium yoelli [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To measure the gene editing activity of dCas9-SSAP in malaria parasites, we first attempted to delete the parasite gene Py05543 , which is nonessential for the growth of blood stages ( 16 ). The plasmid pDEF-dCas9-MCP-RecT- Py05543 containing a 46 bp tag DNA flanked by two homologous regions of Py05543 (403 bp of the 5′-flanking region and 499 bp of the 3′-flanking region) was constructed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the previously reported method ( 7 , 16 ), blood cell samples were collected from the orbital sinus of infected mice and lysed using 1% saponin in phosphate-buffered saline (PBS) to release parasites. These parasites were collected through centrifugation with 12,000 rpm for 3 min, and then the parasite genomic DNAs were isolated using DNeasy Blood kits (QIAGEN), as the template for PCR amplification (TaKaRa).…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of a gene encoding a P. falciparum protein with an AT-rich DNA interaction domain (PfARID) resulted in down-regulation of genes important for gametogenesis, with complete ablation of exflagellation [ 56 ]. Other players include Pb22, APC3 and radial spoke protein 9 (RSP9) in P. berghei [ 57–59 ], p25α in Plasmodium yoelii [ 60 ] and the patatin-like phospholipase, PLP2 in P. falciparum [ 61 ]. For a complete overview of essential regulators of gametogenesis, see [ 44 ].…”
Section: Introductionmentioning
confidence: 99%